The isolation of strand-specific nicking endonucleases from a randomized SapI expression library - Samuelson, James C. (Oxford University Press, 2004)
The Type IIS restriction endonuclease SapI recognizes the DNA sequence 5′-GCTCTTC-3′ (top strand by convention) and cleaves downstream (N1/N4) indicating top- and bottom-strand spacing, respectively. The asymmetric nature of DNA recognition presented the possibility that one, if not two, nicking variants might be created from SapI. To explore this possibility, two parallel selection procedures were designed to isolate either top-strand nicking or bottom-strand nicking variants from a randomly mutated SapI expression library. These procedures take advantage of a SapI substrate site designed into the expression plasmid, which allows for in vitro selection of plasmid clones possessing a site-specific and strand-specific nick. A procedure designed to isolate bottom-strand nicking enzymes yielded Nb.SapI-1 containing a critical R420I substitution near the end of the protein. The top-strand procedure yielded several SapI variants with a distinct preference for top-strand cleavage. Mutations present within the selected clones were segregated to confirm a top-strand nicking phenotype for single variants Q240R, E250K, G271R or K273R. The nature of the amino acid substitutions found in the selected variants provides evidence that SapI may possess two active sites per monomer. This work presents a framework for establishing the mechanism of SapI DNA cleavage.